MODEL PENYAMPAIAN AJARAN ISLAM BERBASIS MODERASI BERAGAMA DALAM PODCAST LOG IN DI CLOSE THE DOOR - Munirul Ikhwan; Amelia Dwi Septianingrum; Happy Susanto; Afiful Ikhwan (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
This research examines the delivery of Islamic teachings based on moderation in the "Log In at Close The Door" podcast on YouTube, which is hosted by Habib Husein Jafar and Onad, with the aim of analyzing the moderation model in the delivery of Islamic teachings and understanding the concept of moderation in the podcast content. The method used is content analysis with a qualitative research type, analyzing in depth 30 podcast episodes that were broadcast during the month of Ramadan 1445 H. The research results show that this podcast is successful in conveying the message of religious moderation with an inclusive and dialogical approach, teaching the importance of harmony, tolerance and openness between religious communities, as well as using digital media effectively to build social harmony and reject extremism